Α‐blockers as medical expulsive therapy for ureteric stones: a Cochrane systematic review. (11th August 2018) - Campschroer, Thijs; Zhu, Xiaoye; Vernooij, Robin W.M.; Lock, Tycho M.T.W.
Abstract : Objective: To assess the effects of α‐blockers compared to standard therapy or placebo for ureteric stones of ≤10 mm confirmed by imaging in adult patients presenting with symptoms of ureteric stone disease. Patients and Methods: We performed a systematic search in multiple databases and grey literature with no restrictions on the language of publication or publication status, up until November 2017. We included randomised controlled trials evaluating ureteric stone passage in adult patients that compared α‐blockers with standard therapy or placebo. Two review authors were independently responsible for study selection, data extraction, and risk‐of‐bias assessment. We performed a meta‐analysis using a random‐effect model. The quality of evidence was assessed on outcome basis according to Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach. Results: We included 67 studies, with 10 509 participants overall. Of these, 15 studies with 5 787 participants used a placebo. Stone clearance: treatment with an α‐blocker may result in a large increase in stone clearance (risk ratio [RR] 1.45, 95% confidence interval [CI] 1.36–1.55; low‐quality evidence), corresponding to 278 more (95% CI: 223–340 more) stone clearances per 1 000 participants. For major adverse events, treatment with an α‐blocker may have little effect (RR 1.25, 95% CI: 0.80–1.96; low‐quality evidence), which corresponds to five more (95% CI four fewer to 19 more) major adverse events per 1 000 participants. Patients treated with α‐blockers may also experience shorter stone expulsion times (mean difference [MD] −3.40 days, 95% CI: −4.17 to −2.63; low‐quality evidence), use less diclofenac (MD −82.41 mg, 95% CI: −122.51 to −42.31; low‐quality evidence) and likely require fewer hospitalisations (RR 0.51, 95% CI: 0.34–0.77; moderate‐quality evidence). Meanwhile, the need for surgical intervention appears similar (RR 0.74, 95% CI: 0.53–1.02; low‐quality evidence). Based on a pre‐defined subgroup analysis (test for subgroup difference, P = 0.002), there may be a different effect of α‐blockers based on stone size with RRs of 1.06 (95% CI: 0.98–1.15; P = 0.16; I ² = 62%) for stones of ≤5 mm vs 1.45 (95% CI: 1.22–1.72; P < 0.0001; I ² = 59%) for stones of >5 mm. We did not find evidence for possible subgroup effects based on stone location or α‐blocker type. Conclusions: In patients with ureteric stones, α‐blockers likely increase stone clearance but probably also slightly increase the risk of major adverse events. Subgroup analyses suggest that α‐blockers may be less effective in smaller (≤5 mm) than larger stones (>5 mm).